Indications for echocardiography of replacement heart valves: a joint statement from the British Heart Valve Society and British Society of Echocardiography - John B Chambers; Madalina Garbi; Norman Briffa; Vishal Sharma; Richard P Steeds (Echo Research and Practice, 2019)
Echocardiography plays a vital role in the follow-up of patients with replacement heart valves. However, there is considerable variation in international guidelines regarding the recommended time points after implantation at which routine echocardiography should be performed. The purpose of routine echocardiography is to detect early structural valve deterioration in biological valves to improve the timing of redo interventions. However, the risk of valve deterioration depends on many valve-related factors (valve design and patient prosthesis mismatch) and patient-related factors (age, diabetes, systemic hypertension, renal dysfunction and smoking). In this statement, the British Heart Valve Society and the British Society of Echocardiography suggest practical guidance. A plan should be made soon after implantation, but this may need to be modified for individual patients and as circumstances change. It is important that patients are managed in a multidisciplinary valve clinic.